Lisp: linguagem de programação para AutoCAD - PACHECO, Alessandro Burguesi (004, 2004)
A linguagem Lisp, que teve seu surgimento na década de 50 durante o projeto de Inteligência Artificial no Massachussetts Institute of Technology (MIT), continua sendo usada até hoje, durante seu processo de evolução vários dialetos foram criados a fim de se adaptarem para a resolução dos problemas nas mais diversas áreas. Entre os vários dialetos destacamos o AutoLisp, que tem sua funcionalidade para aplicaçoes em ferramentas CAD (Computer Aided Design - Desenho auxiliado por computador) , usada especificamente para a criação de rotinas no AutoCAD.

The Lisp language, that had its appearance in the 50's during the Artificial Intelligence project at the Massachusetts Institute of Technology (MIT), and continue in use until nowadays, during its evolution process many different dialects were made with the purpose of adapting themselves for solving problem in the different areas. Among many dialects we give prominence to AUTOLISP, that have its functionalities for applications in CAD tools (Computer Aided Design), used specifically for creation of routines in AutoCad.
Lisp: programming language for AutoCAD
Keywords: Lisp; Autocad; Informação e Comunicação